Evaluation of Clinical Information in Referral of Ultrasound Abdomen. A Cross-Sectional Observational Study - Mahwash Mansoor, Rizwana Rahman Bazai, Noreen Ismail, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the standard of clinical information in referral for ultrasound abdomen in outdoor patients examined at Radiology Department. Study Design: A Cross-Sectional Observational study. Place and Duration of Study. Sandman Provincial Hospital Quetta and Civil Hospital Quetta from October 2021 to July 2022. Materials and Methods: In current study total 3234 patients were selected and referred for abdomen ultrasound. There were 962 (28.7%) patients with clinical information provided for ultrasound while 2265 (70.0%) patients were without any clinical information. All Referral for ultrasound abdomen in Outpatient Ultrasound Department at Sandman Provincial Hospital and Civil Hospital Quetta were reviewed for written clinical information. In present study raw data were collected and analysed in patients with clinical information and without clinical information with SPSS 21. Results: Total Patients referred for ultrasound abdomen were 3234. There were 962 (28.7%) patients with clinical information provided for ultrasound, and 2265 (70.0%) patients without any clinical information. Data showed that most of patients were sent without any clinical information for ultrasound abdomen. Practical implication: Current study was clinical information in referral for ultrasound abdomen which is so important and informative forecast about the expected medical complications. Population can be facilitated through ultrasound because the majority of ultrasound scans are non-invasive and radiation-free ultrasound imaging is quite safe. Soft tissues are clearly visible with ultrasound scanning even if they are difficult to see on x-ray images. Imaging is provided in real-time by ultrasound. There are no known negative effects on humans from standard diagnostic ultrasonography. Conclusion. Standard referrals accompanied with clinical information are very important for ultrasound and all other radiological investigations. If the referral is not properly written with specified clinical information, it can cause miscommunication between radiologist and referring physician, resulting in the overburdening of the radiology department. It then leads to compromised patient care and safety. Keywords: Referral, Standard, Clinical Information, Ultrasound. Radiology, Ultrasonography, investigations, predominately, Abdomen.